Perilaku seksual promiskuitas pada remaja laki-laki Wirobrajan Kota Yogyakarta - Hernawan Isnugroho; Atik Triratnawati; Supriyati Supriyati (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
Promiscuity in sexual behavior in adolescent boys in Wirobrajan, Yogyakarta cityPurposeThis study aimed to obtain a description of the factors that promote promiscuity in sexual behavior and its impact in adolescent boys in Wirobrajan.MethodThis qualitative research used a case study design, using snowball sampling. Data were analyzed by content analysis technique.ResultsThe permissiveness of sexual behavior of teenagers will have an impact, and is easily affected by promiscuity behavior. The influence of peer group or peers is very dominant in the behavior of teen promiscuity. Lack of adolescent awareness about the dangers of promiscuity, the orientation of seeking pleasure and curiosity triggers the behavior of teen promiscuity by exploiting loopholes of rules and lack of control. The confidence and experience of the impact of promiscuity behavior becomes the dominant factor so that teenagers who do not behave with promiscuity do not repeat the behavior. Impact of juvenile promiscuity behavior among others included being ostracized, gonorrhea, syphilis, and genital herpes and other sexually transmitted diseases.ConclusionGreater supervision is needed from various sectors and enforcement of the rules so that the behavior and impact of promiscuity can be minimized. The supervision of teenagers’ association will have an impact on adolescent behavior.